2004
DOI: 10.1021/ef049966c
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption and Optimal Reactor Configuration for Nonthermal Plasma Conversion of N2O in Nitrogen and N2O in Argon

Abstract: The analysis of experimental data, chemical reaction mechanisms, and kinetic modeling data is used to determine the power input and pulsed-corona-discharge reactor configuration that minimizes energy consumption for converting N 2 O in nitrogen and N 2 O in argon, which are model binaries reminiscent of more complex NOx in flue gas systems. Specifically, it is found that inseries reactors are much more energy efficient than a single reactor and more energy efficient than parallel reactors. For example, 12 reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Energy efficiency analysis of NO x conversion in nonthermal plasmas will also be reported separately. 68 …”
Section: Discussionmentioning
confidence: 99%
“…Energy efficiency analysis of NO x conversion in nonthermal plasmas will also be reported separately. 68 …”
Section: Discussionmentioning
confidence: 99%
“…The experimental apparatus and measurement procedures are described in detail elsewhere. 11,13 In brief overview, the pulsed corona discharge reactor used in this work consists of a high-voltage power supply and a pulser/reactor assembly. The pulser/reactor assembly contains a pulsed power generator and pulsed corona discharge tubes.…”
Section: Methodsmentioning
confidence: 99%
“…The feed samples and the reactor effluent samples, collected in small stainless steel cylinders, are analyzed for stable species with a Spectrum 2000 Perkin Elmer Fourier transform infrared ͑FTIR͒ spectrometer with a narrow band mercury cadmium telluride ͑MCT͒ detector, as reported previously. [5][6][7][8][9][13][14][15] For all experimental data, nitrogen oxides other than NO, NO 2 , and N 2 O are not detected by FTIR, which has a detection limit of 5 ppm for each of these species. All experimental data are reproducible within a ±10% error limit, including the FTIR and flow measurement uncertainties.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the energy efficiencies of both NO and NO x decomposition slightly increase with reactor length, but are not strongly dependent on it. Recently, Zhao et al9 investigated the effects of series and parallel operation of multiple PCDRs on energy consumption during N 2 O conversion. They found that series reactors are more energy efficient than a single reactor and parallel reactors.…”
Section: Introductionmentioning
confidence: 99%